Sebuah Nama: Masjid Sultan Mahmud Badaruddin I Jayo Wikramo - Aulia Novemy Dhita; Rieca Nona Mutia (Historia Madania: Jurnal Ilmu Sejarah, 2021)
“What’s in a name?”, the phrase popularized by William Shakepeare, is often used by many people. However, this is not approriate when it’s related to historical fact such as what happened with the changing name of A great mosque in Palembang. This study aims at describing the history of the changing name of that mosque. This research used historical method which consists of heuristic, criticsm, interpretation and historiography. The results shows that the mosque, built in 1738 by Sultan Mahmud Badaruddin I (titled Jayo Wikramo) called by Sulton Mosque, was built by adopting various cultures that were reflected in its architecture, and underwent several renovations. Not only physical renovation, but also the changing name. In 2019, the plant to change the name of this mosque attracted protest from community. However, it was finally agreed that the new name of the Great Mosque of Palembang, namely the Mosque of Sultan Mahmud Badaruddin I Jayo Wikramo. Based on historical notes, there are three names that have been used on this mosque, namely Masjid Sulton, Masjid Agung and  Masjid Sultan Mahmud Badaruddin I Jayo Wikramo. Keywords:  Mosque, Naming, Sultan Mahmud Badaruddin I  Jayo Wikramo, Palembang